Edukasi Tentang Personal Hygine Sekolah Dasar Di Wilayah Kerja Kecamatan Tabunganen - Ernawati, Ernawati; Ariani, Sri Purwanti; Jamilah, Sri; Indria, Rekha (Sahabat Sosial: Jurnal Pengabdian Masyarakat, 2023)
In the nursing field, personal hygiene is considered one of the basic human needs. Personal hygiene refers to individual cleanliness and health practices aimed at preventing the spread of diseases to oneself and others. Hygiene is important because maintaining good personal hygiene minimizes the entry points (portals of entry) for microorganisms that are present everywhere, ultimately preventing individuals from falling. Poor personal hygiene, on the other hand, increases the likelihood of contracting various diseases, such as scabies, infectious diseases, oral and dental diseases, and gastrointestinal illnesses. It can even impact the function of specific body parts, such as the skin. The method used was a demonstration of the six steps of proper handwashing to elementary school students in the Tabunganen sub-district. The results showed that the majority of students were able to wash their hands correctly after the demonstration. It can be concluded that all students were enthusiastic about learning the proper handwashing technique and were able to apply it correctly and effectively. In conclusion, personal hygiene is crucial in preventing the spread of diseases, and maintaining good personal hygiene practices is essential. The study demonstrated the effectiveness of a handwashing demonstration in teaching elementary school students in the Tabunganen sub-district the proper and correct handwashing technique. The findings highlight the students' enthusiasm to learn and their ability to apply the knowledge effectively.